Governança colaborativa na construção de cidades inteligentes: modelo de colaboração entre o setor público local e o sistema S. - Costa, Leandro Dias (2025)
The development of smart cities has gained prominence in academic discussions and governance structures. Among the various characteristics of this city concept, this work emphasizes the adoption of an innovative collaborative governance framework for formulating urban policies, aiming to improve the quality of life of residents. Therefore, the objective of this study is to propose a collaborative framework between local public governance and the third sector, specifically the S System, to boost economic and social development, aiming to contribute to the smarter cities. This research, which is basic in nature, uses a qualitative approach, and is exploratory in nature. It is based on a Systematic Literature Review (SLR) using the Methodi Ordinatio methodology, which aligns the smart city perspective with the participation and collaboration of the third sector. A case study was used as the technical procedure. The results demonstrate that the collaboration between the public sector and the S System in Palmas (Tocantins), resulted in the creation of a training program for young people, which provided access to more qualified jobs and increased the employability of participants. It is hoped that this research will help in understanding how different sectors of society can collaboratively contribute to the construction of smarter cities, and that it will serve as a guiding instrument for more effective and innovative governance practices.